2005
DOI: 10.1093/jn/135.4.808
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Vitamin A Deficiency in Long-Term African Refugees,

Abstract: Five cross-sectional surveys were conducted in African refugee camps to assess the level of iron deficiency anemia and vitamin A deficiency in populations dependent on long-term international food aid and humanitarian assistance. The prevalence of anemia in children [hemoglobin (Hb) <110 g/L] was high, with >60% affected in 3 of 5 camps. Iron deficiency [serum transferrin receptor (sTfR) >8.5 mg/L] was also high, ranging from 23 to 75%; there was also a strong ecological correlation between the prevalence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…A study of Bhutanese refugee children in Nepal documented a prevalence of 43.3 % in 2007, prior to introduction of micronutrient supplementation [35]. A study of refugees in long-term African refugee camps found even higher prevalence estimates among children in camps in Kenya (61.3 %), Uganda (72.9 %), and Ethiopia (62.9 %) [8]. High prevalence of anemia among refugees has been attributed in part to the reliance on food rations in camps, an explanation consistent with our finding that prevalence among the camp based refugees in Za’atri was higher than in non-camp based refugees in Jordan and in Lebanon [7, 8, 35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of Bhutanese refugee children in Nepal documented a prevalence of 43.3 % in 2007, prior to introduction of micronutrient supplementation [35]. A study of refugees in long-term African refugee camps found even higher prevalence estimates among children in camps in Kenya (61.3 %), Uganda (72.9 %), and Ethiopia (62.9 %) [8]. High prevalence of anemia among refugees has been attributed in part to the reliance on food rations in camps, an explanation consistent with our finding that prevalence among the camp based refugees in Za’atri was higher than in non-camp based refugees in Jordan and in Lebanon [7, 8, 35].…”
Section: Discussionmentioning
confidence: 99%
“…A study of refugees in long-term African refugee camps found even higher prevalence estimates among children in camps in Kenya (61.3 %), Uganda (72.9 %), and Ethiopia (62.9 %) [8]. High prevalence of anemia among refugees has been attributed in part to the reliance on food rations in camps, an explanation consistent with our finding that prevalence among the camp based refugees in Za’atri was higher than in non-camp based refugees in Jordan and in Lebanon [7, 8, 35]. In our assessments of non-camp based refugee populations, anemia levels were more consistent with the host populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity can affect health and quality of life either directly or indirectly through nutritional status [7], and is linked to mental illness in several ways [8]. Refugees represent an “at risk” population for nutrient deficiencies, such as vitamin B12 and iron [911], which could predispose them to depression [12]. Added to this, the psychological distress individuals may experience as a result of not being able to afford food, not having adequate access to nutritious or culturally appropriate food or being able to feed their families, further compounds this risk of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Refugees and other populations dependent on food aid are potentially at greater risk of anaemia and Fe deficiency (3)(4)(5) . Food rations provided to such populations are frequently deficient in Fe and other micronutrients (6,7) .…”
mentioning
confidence: 99%